-5=-2+l

Simple and best practice solution for -5=-2+l equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5=-2+l equation:


Simplifying
-5 = -2 + l

Solving
-5 = -2 + l

Solving for variable 'l'.

Move all terms containing l to the left, all other terms to the right.

Add '-1l' to each side of the equation.
-5 + -1l = -2 + l + -1l

Combine like terms: l + -1l = 0
-5 + -1l = -2 + 0
-5 + -1l = -2

Add '5' to each side of the equation.
-5 + 5 + -1l = -2 + 5

Combine like terms: -5 + 5 = 0
0 + -1l = -2 + 5
-1l = -2 + 5

Combine like terms: -2 + 5 = 3
-1l = 3

Divide each side by '-1'.
l = -3

Simplifying
l = -3

See similar equations:

| 9(2y-8)-(2y+2)= | | f(x+6)=x^2+9x-1 | | (176-y)=(115+x) | | 5n-n+5=13 | | 4x^2+y^2+2y=0 | | -3=m-3 | | 3=l-5 | | 4n-2n+10=22 | | -9+y=7 | | f(x)=x^2+9x-1 | | 1.05t+0.63=-0.07t | | 4x+2(8)=4x(9) | | 10n+2=22 | | 13-6b=3+11b | | 9n+18=36 | | (99+x)=(176+y) | | -9(x+3)+3x+6=5x+9 | | 6.75t+7=15.5t+14 | | 4568b-4=7 | | -v+2=3 | | 116=-4(-4y)-9(2y)+y | | (w*3-9)+(w+4)=(w*3-9)+(w+4) | | 2x+3y=5.13 | | 16+b^2+6b=0 | | 4y^6(y^2+9y+2)= | | 8n^2-3n-16=24 | | -10+3x=-4 | | X+y=y+x+200 | | 57=3v+3 | | 89-116=-4(-4y)-9(2y) | | 4x+6+6x=36 | | x+y+z=2000zxy |

Equations solver categories